Offshoring and sequential production chains: A general-equilibrium analysis - Philipp Harms; Jaewon Jung; Oliver Lorz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
In this paper, we develop a two-sector general equilibrium trade model which includes offshoring, sequential production, and endogenous market structures. We analyze how relative factor endowments and various forms of globalization and technological change affect equilibrium offshoring patterns. We show that, against common belief, a reduction in trade costs lowers the range of tasks offshored even though the aggregate volume of offshoring may increase.
Keywords: D24; F10; F23; L23; 330; Offshoring; sequential production; global production chain; task trade